2002
DOI: 10.1029/2002gl015221
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of Brazil Current rings observed from AVHRR: 1993 to 1998

Abstract: [1] A 6-year time series of sea surface temperature fields derived from NOAA polar-orbiter AVHRR 5-day composites is used to estimate the lifetime, size, and trajectory of 43 warm-core rings shed by the Brazil Current at the Southwestern Atlantic region in a consistent fashion for the first time. Ring lifetimes range from 11 to 95 days, and are not bi-modal as is the case for the Gulf Stream anticyclones. Translational speeds range from 4.2 to 27.2 km/day with a mean value of 13.1 km/day. After formation, ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 16 publications
7
47
1
6
Order By: Relevance
“…Lebedev and Nof 1997;Witter and Gordon 1999;Wainer et al 2000;Lentini et al 2002). The study of Arruda et al (2004) suggests that temporal variations in BC transport upstream of the zone can affect the detachment of intrusion eddies at the BMCZ.…”
Section: September 2012mentioning
confidence: 99%
“…Lebedev and Nof 1997;Witter and Gordon 1999;Wainer et al 2000;Lentini et al 2002). The study of Arruda et al (2004) suggests that temporal variations in BC transport upstream of the zone can affect the detachment of intrusion eddies at the BMCZ.…”
Section: September 2012mentioning
confidence: 99%
“…The search area is an "ellipse" with a zonally oriented major axis. The western boundary of the ellipse is the distance from the eddy core, which is determined from the maximum value between 1.75 times the daily long Rossby wave propagation distance [41] and the mean mesoscale eddy propagation distance on the order of 10 km per day [42,43]. However, since 150 km was set as the minimum search range for weekly data by Chelton et al [2] and we used daily data, the maximum daily travel distance of an eddy should be approximately 21 km.…”
Section: Eddy Trackingmentioning
confidence: 99%
“…This decay in the chlorophyll concentration at the eddy cores, was also observed on SST and SLA signals as a consequence of the mixing of the eddies with warmer and low chlorophyll concentration waters. By following the chlorophyll maximum in the eddy centers, the authors estimated a propagation velocity of ∼12 km/day, which was in accordance with the results of Lentini et al (2002). Moreover, To summarize, the dynamics of the BMC is dominated by mesoscale eddies.…”
Section: The Brazil-malvinas Confluencesupporting
confidence: 70%
“…The surface temperature at the eddy core was of 19. A robust statistics of warm-core mesoscale eddies shed by the BC into the BMC region was presented by Lentini et al (2002). The authors identified and followed a total of 43 anticyclonic eddies using 6 years of SST data from AVHRR.…”
Section: The Brazil-malvinas Confluencementioning
confidence: 99%